2014
DOI: 10.1146/annurev-linguist-030514-124824
|View full text |Cite
|
Sign up to set email alerts
|

Language and Speech in Autism

Abstract: Autism is a developmental disability characterized by atypical social interaction, interests or body movements, and communication. Our review examines the empirical status of three communication phenomena believed to be unique to autism: pronoun reversal (using the pronoun you when the pronoun I is intended, and vice versa), echolalia (repeating what someone has said), and a reduced or even reversed production-comprehension lag (a reduction or reversal of the well-established finding that speakers produce less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 48 publications
(13 reference statements)
0
28
0
1
Order By: Relevance
“…Indeed, autism is associated with a wide range of language abilities. While some autistic people are minimal or non-verbal, others have typical ( Brignell et al, 2018 ) or enhanced ( Hyltenstam, 2016 ) language skills, with or without peculiar speech patterns ( Gernsbacher et al, 2016 ). The presence of these linguistic capacities in many autistic people suggests that learning and achieving fluency in more than one language is also possible for autistic people, as it is for their non-autistic peers.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, autism is associated with a wide range of language abilities. While some autistic people are minimal or non-verbal, others have typical ( Brignell et al, 2018 ) or enhanced ( Hyltenstam, 2016 ) language skills, with or without peculiar speech patterns ( Gernsbacher et al, 2016 ). The presence of these linguistic capacities in many autistic people suggests that learning and achieving fluency in more than one language is also possible for autistic people, as it is for their non-autistic peers.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, autism is associated with a wide range of language abilities. While some autistic people are minimally-or non-verbal, others have typical (Brignell et al, 2018) or enhanced (Hyltenstam, 2016) language skills, with or without peculiar speech patterns (Gernsbacher et al, 2016). The presence of these linguistic capacities in many autistic people suggests that learning and achieving fluency in more than one language is also possible for autistic people, as it is for their non-autistic peers.…”
Section: Introductionmentioning
confidence: 99%
“…Recent narrative reviews have sought to describe pronoun use within the context of overall language development in individuals with autism (Arunachalam & Luyster, 2018; Gernsbacher et al, 2016; Naigles & Tek, 2017; Ying Sng et al, 2018). Gernsbacher et al (2016) present evidence that suggests language development in children with autism is varied but follows a normative production-comprehension lag. Citing studies that illustrate pronoun errors and repetitive speech as evident in TD children, they conclude these phenomena are not unique to individuals with autism.…”
Section: Previous Reviewsmentioning
confidence: 99%
“…While past reviews have highlighted heterogeneous language development skills, they have also suggested the need for a more focused review that compares what is known about language development about pronoun use in children with autism compared with their TD peers (i.e. Gernsbacher et al, 2016; Naigles & Tek, 2017; Ying Sng et al, 2018).…”
Section: Present Studymentioning
confidence: 99%